Evaluation of the CUALTOS Degree in Medicine from the GRANA Model - Donato Vallín González; Alfredo Luna Soto; Francisco Bernabe Ramos; Benjamín Guzmán Flores; Jorge Arturo Pelayo López (RIDE Revista Iberoamericana para la Investigación y el Desarrollo Educativo, 2020)
The article is based on an academic-administrative evaluation of the Bachelor of Medicine of the Los Altos University Center (CUALTOS) of the University of Guadalajara, located in the city of Tepatitlán de Morelos, Jalisco, Mexico. The model used is called GRANA and its methodology is based on a decimal qualitative and quantitative evaluation system composed of 10 items or dimensions, 100 items and 1000 qualitative indicators. One of the 10 items is called: "Social impact of training", that is, the relevance and quality with which the students of this career associated with the surrounding region are trained. There are three moments in which the evaluation was carried out: The internal evaluation, the external evaluation and the verification of evidence. The means used for the integration of the processes was with the use of the SIEVAS computer platform, which means: online evaluation and monitoring system as a facilitator of the entire process of its stages and allows interaction between evaluators. The tools it has to facilitate the evaluation are: meanings, contexts, bibliographic references, glossary, decimal scale to qualify quality levels, fields to integrate strengths, weaknesses, the permanent improvement plan and formats to integrate statistics in retrospect and prospective. The evaluation system facilitates the computer availability to incorporate supporting documents and websites that help the evaluation process. It also has charts that are built automatically as the evaluation is incorporated into the platform. The internal evaluation was carried out by a CUALTOS committee made up of: three professors, two managers and a student, linking graduates and employers associated with the degree to this process. The participating external evaluators were from: Venezuela, Brazil and Spain with a specialty in the evaluated discipline and with experience in evaluation processes in the field of the discipline.